Gender and child feeding practices in Belize- a trend analysis - Oladeji, Olusola; Beer, Natalia L.; Baitwabusa, Angella E.; Faber, Robyn D. (International Journal Of Community Medicine And Public Health, 2024)
The study aimed to determine the trend and gender differences in child feeding practices in Belize based on consecutive multiple indicator cluster surveys (MICS) using a retrospective quantitative study. The secondary analysis of the last consecutive MICS data from 2006, 2011 and 2015-16 was done using SPSS software version 23. Association between gender and feeding practices was determined by bivariate analysis using chi-square test and p value < 0.05 was considered statistically significant. There was increased gender differentials in optimal feeding practices in children over the study period. The inequalities between male and female increased over the study period for most of the feeding practices except for exclusive breastfeeding where the gender inequality diminished. The exclusive breastfeeding rate among female children was higher than among male children in the three surveys but significant only in 2006 and 2011 surveys, p<0.05. More female children were timely initiated on complementary feeding compared to male children in the three surveys and was found to be significant in 2006 and 2015 surveys, p<0.05. Minimal meal frequency and minimal dietary diversity was higher among female than among male but there was no significant difference(p>0.05). The study shows evidence of gender differential in feeding practices. There is need to improve gender sensitization in terms of feeding practices within the households; develop and implement culturally appropriate gender sensitive guidance and approaches on optimum infant and young child feeding practices in the country.